Subacute transverse myelitis as a clinical presentation of neurobrucellosis - Juan José Díaz-Vintimilla; Luis Adrián Rosales Hernández; Rogelio Zapata-Arenas; Sokani Sánchez-Montes; Ingeborg Becker (Journal of Infection in Developing Countries)
Brucella melitensis is the main cause of human brucellosis worldwide and is considered the most virulent and neurotropic species. In Mexico, this species is considered endemic, being reported since the first decade of the 20th century. Here we present a case of subacute transverse myelitis with the isolation and identification of B. melitensis as the causative agent of Neurobrucellosis in a female patient from the coastal state of Guerrero, Mexico.